PENGARUH WORK LIFE BALANCE DAN DUKUNGAN SOSIAL TERHADAP FREELANCER DI MEDIA SOSIAL - Yusri, Rexanova Khansa; Utama, Rony Edward (Taksasila Edukasi Insani, 2026)
This study employed a quantitative method with a survey approach. The research population consisted of students who work as freelancers on social media, with a total sample of 96 respondents selected using a specific sampling technique. Data were collected through questionnaire distribution and analyzed using multiple linear regression analysis with the assistance of SPSS version 30. The results show that, partially, work-life balance has a negative and significant effect on freelancers, while social support has a positive and significant effect on freelancers. Simultaneously, work-life balance and social support have a significant effect on freelancers on social media. These findings indicate that social support plays an important role in encouraging students to engage in freelance work, while work-life balance serves as a key consideration in determining freelance career choices.Keywords : Work-life balance, Social support, Freelancers